A inclusão escolar de alunos com deficiência visual a partir da percepção de professores de matemática, professores do atendimento educacional especializado e gestores educacionais - Petró, Caroline da Silva (2014)
This paper had as main objective to understand the school inclusion process of students with visual impairments from the perception of mathematics teachers, teachers of specialized educational services and educational managers. With this, we attempted to identify how mathematics teachers and specialized educational services teachers are developing their roles, to identify the supports offered by specialized educational services to visually impaired students and to mathematics teachers, identifying the relationships established between specialized educational services teachers, mathematics teachers and students with visual impairment, to analyze how mathematics teachers, specialized educational services teachers and educational managers perceive school inclusion of students with visual impairments. Thirteen subjects were interviewed: three mathematics teachers, four specialized educational services teachers, two students with visual impairments from high school, two educational managers who work in sectors related to school inclusion and also, two professionals who work to qualify teachers to operate at specialized educational services with Technology assistive applied to the educational context. The research was a qualitative nature, one type of case study, and had their data analyzed by Textual Discourse Analysis. In this analysis, three categories emerged and they termed as, "The different roles of those involved in scenario of school inclusion", "The role of institutions" and also "The school inclusion process of students with visual impairments" In the first category discusses the role assigned to mathematics teachers and to specialized educational services teachers, also, what is expected from students with visual impairments and from their families in the view of the research subjects. In the second category are evident as interviewees perceive the school and the State assignments so the inclusion of students with visual impairment indeed occurred. In the third category discusses how the process is going to school inclusion of students with visual impairments, as relationships are established between the subject and the resources that encouraged inclusiveness. Among other results, the analysis showed that students with visual impairments are being well covered with teaching resources, but still lack coordination and partnership among mathematics teachers and the specialized educational services teachers because they are working in isolation from others.